PEMANFAATAN OLAHAN DENGAN BAHAN DASAR DAUN KELOR UNTUK MENINGKATKAN STATUS IMUNITAS IBU HAMIL SEBAGAI BENTUK UPAYA PENCEGAHAN PENULARAN COVID-19 - Susmiati; Indah Jayani; Sri Haryuni; Kun Ika Nur Rahayu; Endang Mei Yunalia; Idola Perdana Sulistyoning Suharto (Universitas Kadiri, 2025)
Pregnant women are one of the vulnerable groups to the transmission of Covid-19 which can transmit the Covid-19 virus to the fetus they are carrying. Various efforts to increase immunity status are carried out so that pregnant women can survive during the Covid-19 pandemic, starting from exercise, minimizing stress and providing nutritional supplements and food. Moringa leaves are one of the basic food ingredients with high nutritional value that are cheap and easy to obtain. The content of Moringa leaves as antioxidants and increases immunity status. The purpose of this activity is to increase the knowledge of pregnant women in the use of processed products from Moringa leaves as an effort to increase the immunity status of pregnant women. The activity method includes the preparation stage, implementation in the form of counseling, and evaluation of activities. Based on the results of the implementation of this activity, it is hoped that the use of processed moringa leaves as other food ingredients can be developed to increase the immunity status of pregnant women.